Mengatasi kemiskinan: Memahami akar masalah, tantangan global, dan solusi berkelajutan untuk meningkatkan kesejahteraan masyarakat - Ummah, Fina Zaimatul (Maliki Interdisciplinary Journal, 2024)
Poverty is one of the greatest challenges the world faces today, affecting various aspects of social, economic, and environmental life. The article examined the root of poverty by focusing on structural causes such as inequality in access to education, health, and jobs, as well as uneven economic policy impacts. In addition, the article discussed global challenges that worsen poverty, including climate change, rapid urbanisation, and the health crisis. Sustainable solutions to poverty and improve public welfare are also described, ranging from local economic empowerment, improved education and health quality, to inclusive environmental policies. With a comprehensive and collaborative approach, the article highlights the importance of strategies that focus not only on short-term help but also on sustainable development to ensure the longterm welfare of the entire community.